Optimizing Halal and Islamic Legal Literacy for MSMEs: Strategies to Enhance the Adoption of Sharia Products in Indonesia - Amrin, Amrin; Yono, Yono; Zakaria, Zakaria; Vustany, Rovi Octaviano; Agus, Rizal (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
This study aims to explore and develop an effective halal literacy strategy for MSMEs in Indonesia, with a focus on increasing the adoption of Islamic financial products. This study also evaluates the success of various implemented halal literacy education and training programs, including their compliance with Islamic legal regulations and national Sharia governance. The research methodology employed a qualitative approach, collecting data through observations and interviews with various MSMEs in Bima City, West Nusa Tenggara. Data analysis was conducted using a SWOT approach. The research findings indicate that a comprehensive halal literacy strategy should include the provision of easy-to-understand educational materials, ongoing training, and awareness-raising through mass media campaigns, supported by strengthening MSMEs' understanding of Islamic legal obligations, halal certification requirements, and Islamic financial regulations. The results of this study emphasize the importance of an integrated approach to improving MSMEs' understanding of Islamic financial products, their legal basis, and the benefits they offer. With increased halal literacy, including Islamic legal literacy, MSMEs can utilize Islamic financial products to support sustainable business growth in accordance with Islamic principles and applicable Islamic financial laws. This study also provides practical recommendations for policymakers, financial institutions, and MSME support organizations to facilitate increased halal literacy, strengthen legal awareness, and expand MSME access to Islamic financial products in Indonesia.